Análise do território: um instrumento interventivo na prática do programa de saúde da família - Bôas, Heloísa Strazzer Vilas (2007)
This work objective is to detect the importance of the concept of territory between the teams of the Programa de Saúde da Família PSF (Family Health Program), in order it becomes an effective diagnosis and intervention tool. Brazilian Ministry of Health recognizes the relevance of the concept of territory as a work instrument since the PSF was created in 1994. However, it is perceptible that, despite the concept appearing in the training of the PSF teams, it is not used as an essential in the practice. The research methodology intended to apprehend the theoretical and practical dimensions of the concept of territory. To the bibliographic and document analysis it was added interviews with the coordinators of the Programa de Saúde da Família and focal groups with the PSF teams of three cities belonging to the Diretoria Regional de Saúde XXI DIRXXI (Health Regional Branch XXI) of the State of São Paulo: Jacareí, Jambeiro e Caraguatatuba. Regardless the demographic, social and local health differences, which imply different needs, the teams recognized that the question of the territory as work instrument was part of the initial given training. However, in practice, it was noticed that the concept of territory, beyond not being well understood, it was neither up to date nor it was reinforced in late supervisions. This leads, among others, to a block of the teams creativity, to an incomplete use of the available resources, to not felling responsible for the health problems and for the families in the area, to not establishing needed partnerships with others public policies, and to a lack of mobilization of local forces. In short, a considerable loss for the population health and the impoverishment of the guidelines of the PSF in the practice